2005
DOI: 10.1038/sj.jp.7211278
|View full text |Cite
|
Sign up to set email alerts
|

Home-Based Neonatal Care: Summary and Applications of the Field Trial in Rural Gadchiroli, India (1993 to 2003)

Abstract: High levels of neonatal mortality and lack of access to neonatal health care are widespread problems in developing countries. A field trial of home-based neonatal care (HBNC) was conducted in rural Gadchiroli, India to develop and test the feasibility of a low-cost approach of delivering primary neonatal care by using the human potential available in villages, and to evaluate its effect on neonatal mortality. In the first half of this article we summarize various aspects of the field trial, presented in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
109
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(116 citation statements)
references
References 28 publications
(22 reference statements)
1
109
1
Order By: Relevance
“…These findings are similar to other studies of low resource countries. 1,[3][4][5]11,12 All these studies identified that malnutrition, lack of nutritional education and lack of early antenatal care are significant risk factors for low birth weight babies.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to other studies of low resource countries. 1,[3][4][5]11,12 All these studies identified that malnutrition, lack of nutritional education and lack of early antenatal care are significant risk factors for low birth weight babies.…”
Section: Discussionmentioning
confidence: 99%
“…gestational age <32 weeks) and with very low birthweight (VLBW) (<1,500 g) have mortality rates of over 50% in many low-resource settings and are at a higher risk for long-term disabilities and impairments. [2][3][4] One of the Millennium Development Goals (MDG-4) is to reduce the child mortality (under 5 years) rate by two-thirds by the year 2015 from a base line in 1990. The World Health Organization estimates that a significant proportion (40%) of all under 5 deaths occur in the neonatal or perinatal (0 to 28 days of life) periods.…”
Section: Introductionmentioning
confidence: 99%
“…The health activists help mothers access antenatal care, encourage delivery in a health-care institution, offer home-based neonatal care during the first 7 days of life and provide counselling on community health and nutrition through home visits and community meetings. 4,5 While these initiatives should help improve neonatal survival, achieving adequate and equitable coverage is difficult. 6,7 Recent evaluations found that the poorest mothers did not always receive payments under the Janani Suraksha Yojana, that institutional delivery was not necessarily synonymous with good obstetric care and that the Janani Suraksha Yojana had not yet resulted in a large reduction in neonatal mortality.…”
Section: Introductionmentioning
confidence: 99%